Jewish exiles and European thought during the Third Reich - Weinstein, David 1949-; Zakhai, Avihu 1945- (Cambridge University Press, 2017)
"Hans Baron, Karl Popper, Leo Strauss and Erich Auerbach were among the many German-speaking Jewish intellectuals who fled continental Europe with the rise of Nazism in the 1930s. Their scholarship, though not normally considered together, is studied here to demonstrate how, despite their different disciplines and distinctive modes of working, they responded polemically in the guise of traditional scholarship to their shared trauma. For each, the political calamity of European fascism was a profound intellectual crisis, requiring an intellectual response which Weinstein and Zakai now contextualize, ideologically and politically. They exemplify just how extensively, and sometimes how subtly, 1930s and 1940s scholarship was used not only to explain, but to fight the political evils that had infected modernity, victimizing so many. An original perspective on a popular area of research, this book draws upon a mass of secondary literature to provide an innovative and valuable contribution to twentieth-century intellectual history"...
Includes bibliographical references and index
Keywords: Baron, Hans -- 1900-1988; Popper, Karl R. -- (Karl Raimund) -- 1902-1994; Strauss, Leo; Auerbäck, Erich; Auerbach, Erich -- 1892-1957; Strauss, Leo -- 1899-1973; Popper, Karl R. -- 1902-1994; Geschichte 1933-1945; Jewish philosophy -- 20th century; Philosophy, Modern -- 20th century; Jewish scholars -- Germany; Holocaust, Jewish (1939-1945); Exil; Intellektueller; Juden; Deutschland